UNELE PRECIZĂRI ASUPRA CONCEPTULUI DE COMPETENŢĂ ŞCOLARĂ - USM ADMIN (Moldova State University, 2009)
In this article the concept of competence and the indicators are analyzed. In the result, there have been motivated some characteristics and definitions of the competence.